EFFECT OF TUBER CUTTING AND CROPPING DENSITY AGAINST GROWTH AND YIELD OF ONION (Allium ascalonicum L.) - Syahir Nedi Purba; Ansoruddin Ansoruddin; Lokot Ridwan Batubara (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was carried out at Durian street, Kisaran Naga Village, Kisaran Timur, AsahanDistrict, North Sumatera. The study was conducted in April to June 2017. This research wasarranged based on Factorial Randomized Block Design with 2 treatment factors and 3replications. The first factor was cutting of tubers with 4 levels ie: P0 = without cutting tuber, P1 = cutting tuber of 1/3 of shoot, P2 = cutting tuber of 1/4 of shoot, and P3 = cutting tuber of 1/5 of part shoots. The second factor of plant density with 3 levels of spacing is J1 = 20 cm x 10 cm, J2= 20 cm x 15 cm, and J3 = 20 cm x 10 cm. The results showed that tuber cutting treatment had significant effect on all observed variables, whereas cutting of tuber 1/3 of shoot (P1) was the best treatment. Treatment of plant density had significant effect on all observed variables, where the density with plant spacing of 20 cm x 20 cm (J3) was the best treatment. The interaction between tuber cutting and plant density had no significant effect on all observed variables.